1979
DOI: 10.1021/jo00394a044
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of dihydropyridines. 9. Hydride transfer from 1,4-dihydropyridines to sp3-hybridized carbon in sulfonium salts and activated halides. Studies with NAD(P)H models

Abstract: ether gave pure la (30 mg, 15%): mp 188-189 "C; NMR7 (acetone-d6 + DzO) d 3.04 (s, 3, CH3), 4.38 (d of q, 1, H3), 4.78 (d, 1, H4), 6.08 (d of d, 1, Hz), 7.25-8.25 (m, 7, H1 and aromatic), 8.73 trans-3,4-Dihydroxy-anti-1,2-epoxy-1,2,3,4-tetrahydro-7methylbenz[a]anthracene (2). A solution of la (23 mg, 0.083 mmol) and rn-chloroperbenzoic acid (230 mg) in 25 mL of dry THF was stirred under Nz for 2 h at room temperature. The solution was diluted with ether, washed twice with 10% aqueous NaOH solution and water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(43 citation statements)
references
References 3 publications
0
43
0
Order By: Relevance
“…2 m distance). Addition of SCHEME 2 Dye-accelerated photoreduction of phenacyl sulfonium salt 2 and related substrates (refs 16,17 ) 1 mole % of [Ru(bpy) 3 ]Cl 2 , TPP, or eosin disodium salt led to acceleration of the irradiated reactions resulting in complete conversions within significantly shorter reaction times of 0.3, 1 and 3 h, for the three dyes, respectively. The authors suggested that light-induced single-electron transfer steps are responsible for the observed sulfonium salt reduction and proposed that the large acceleration effect of [Ru(bpy) 3 ]Cl 2 might be due to the involvement of this photoredox catalyst in the single-electron transfers (SET) 16 .…”
Section: Early Examples From the 1970s To 1990smentioning
confidence: 99%
See 3 more Smart Citations
“…2 m distance). Addition of SCHEME 2 Dye-accelerated photoreduction of phenacyl sulfonium salt 2 and related substrates (refs 16,17 ) 1 mole % of [Ru(bpy) 3 ]Cl 2 , TPP, or eosin disodium salt led to acceleration of the irradiated reactions resulting in complete conversions within significantly shorter reaction times of 0.3, 1 and 3 h, for the three dyes, respectively. The authors suggested that light-induced single-electron transfer steps are responsible for the observed sulfonium salt reduction and proposed that the large acceleration effect of [Ru(bpy) 3 ]Cl 2 might be due to the involvement of this photoredox catalyst in the single-electron transfers (SET) 16 .…”
Section: Early Examples From the 1970s To 1990smentioning
confidence: 99%
“…The authors suggested that light-induced single-electron transfer steps are responsible for the observed sulfonium salt reduction and proposed that the large acceleration effect of [Ru(bpy) 3 ]Cl 2 might be due to the involvement of this photoredox catalyst in the single-electron transfers (SET) 16 . Later on, results of a more detailed mechanistic study were disclosed 17 . Although the authors did not arrive at a definitive conclusion about the exact role of [Ru(bpy) 3 ] 2+ in this process, an impressively insightful discussion of the gathered body of evidence was presented 17 .…”
Section: Early Examples From the 1970s To 1990smentioning
confidence: 99%
See 2 more Smart Citations
“…[44] Phenyldimethylsulfonium trifluorosulfonate (PDMS + CF 3 SO 3 -) and phenylmethylphenacylsulfonium tetrafluoroborate (PMPS + BF 4 -) were synthesized according to the literature. (45,46) Tin(IV) chloride (1.0 m solution in heptane, from Aldrich) was used as received. VCZ (extra pure, from Nacalai Tesque Inc. Japan) was recrystallized from methanol.…”
Section: Methodsmentioning
confidence: 99%